Common errors in statistics (and how to avoid them) - Good, Phillip I. 1937-; Hardin, James W. 1963- (Wiley, 2009)
"A straightforward discussion of basic statistical methods, presentations, approaches, and modeling techniques ... This book addresses popular mistakes often made in data collection and provides a guide to accurate statistical analysis and reporting"--From publisher's description.
Keywords: Statistik; Statistics; Denkfehler; Irrtum